Longevity of Horseweed Seed Bank Depending on the Burial Depth - VARGAS,A.A.M. (2018)
ABSTRACT: Horseweed (Conyza spp.) is considered as one of the major weeds occurring in the agricultural areas of South America, especially in Brazil. This species stands out from the other weeds due to characteristics such as large seed production, continued seed production, dispersion over long distances and resistance to 5-enolpyruvoylshikimate 3-phosphate (EPSP) and acetolactate synthase (ALS) inhibiting herbicides, features that increase their management. Therefore, this study aimed at determining the physiological quality and longevity of horseweed seeds over 12 months. The experiment was established under field conditions, using a randomized block design with four replications. Fifty horseweed seeds were distributed into 50 g of dry soil, placed in permeable nylon mesh bags (10 x 10 cm), which were buried at 1, 2, 4 and 8 cm of depth. Each month, for 12 months, samples were collected and washed with water, and the remaining seeds were submitted to germination test. The percentage (%) of remaining seeds, germination, abnormal seedlings, dead seeds, dormancy and viability were evaluated. It was found that the horseweed seed bank was reduced by 59 % over 12 months. Moreover, horseweed seeds develop a secondary dormancy, regardless of the burial depth. In addition, an increased burial depth increases longevity and physiological seed quality.